2021
DOI: 10.1016/j.dcn.2021.100933
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental differences in child and adult number processing: An fMRI-based validation of the triple code model

Abstract: Highlights Overlapping neural responses to number discrimination tasks in adults and children. Ontogenetic maturation of language regions may constrain verbal number processing. Neural correlates of effortful number discrimination were similar across age groups. Prefrontal activity attributed to children’s number processing was not replicated. Results indicative of mature number discrimination abilities around 11 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…Our results suggest that simple numerical magnitude discrimination control trials may be suboptimal as a control and are better suited to distinguish preadolescent groups. Recent work suggests that the age of our sample (11–12) is when network recruitment for magnitude discrimination begins to compare to adults ( Skagenholt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that simple numerical magnitude discrimination control trials may be suboptimal as a control and are better suited to distinguish preadolescent groups. Recent work suggests that the age of our sample (11–12) is when network recruitment for magnitude discrimination begins to compare to adults ( Skagenholt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study builds on prior functional magnetic resonance imaging (fMRI) research from our lab ( Skagenholt et al, 2021 ), examining middle-school-aged children’s and young adults’ neural activity elicited by Arabic digit, number word, and nonsymbolic numerical dot array discrimination tasks (i.e., selecting the numerically greater alternative). Acting as a direct empirical validation of previous meta-analytic investigations into the predictions of the TCM (e.g., Arsalidou and Taylor, 2011 ; Arsalidou et al, 2018 ), the results indicated minor neural activity differences between the two age-groups across tasks.…”
Section: Introductionmentioning
confidence: 99%
“…One of them suggested weaker activation for children in third and sixth grades vs. adults in occipital areas during non-symbolic magnitude comparisons, in the inferior frontal gyrus when performing (symbolic) exact calculations and in the intraparietal sulcus across tasks (Kucian et al, 2008). Another study showed weaker activations in leftperisylvian language areas in 10-12-year-old children compared to adults during a verbal number comparison task, but not during an Arabic digit comparison task (Skagenholt et al, 2021). In addition, an fMRI study examined longitudinally 8-11-year-old children with and without developmental dyscalculia, using a numerical order judgment task and two time points during a period of 4 years (McCaskey et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is currently limited evidence on how visual specialization to numbers develops in childhood, during the acquisition of numeric and arithmetic skills. Some fMRI studies compared children and adults using explicit tasks involving number comparisons and simple operations ( Kucian et al, 2008 ; Skagenholt et al, 2021 ). One of them suggested weaker activation for children in third and sixth grades vs. adults in occipital areas during non-symbolic magnitude comparisons, in the inferior frontal gyrus when performing (symbolic) exact calculations and in the intraparietal sulcus across tasks ( Kucian et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%